Effects of Salinity on Soybean (Glycine max [L.] Merr.) DT26 Cultivar - Hang, Ha Thi; Mai, Le Quynh (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: Nowadays, climate change is the serious environment problem affecting the Earth. Higher earth temperatures melt iceberg raising the sea-level that causes salinity. Effects of salinity on growth and development of plants, specially crops, are one of the most concerns of plant physiologists.  It has been proven that the difference among cultivars provides important sources for high quality breeding. Soybean ( Glycine max [L.] Merr) is one of the few plants that can supply all eight essential amino acids. For a long time, it has become a very important crop inVietnam. The effects of salt stresses ranging from lower to higher levels established by a gradient of NaCl concentration on the growth of soybean DT26 cultivar were studied. DT26 is the most popular cultivar of soybean used by farmers inVietnam. The rate of germination, the length and fresh weight of shoots and roots, the content of chlorophyll and the content of proline were assessed in this study. Generally, at low salt concentration, the length of roots, the fresh weight of both shoots and roots increased, but under high salinity conditions these parameters were decreased. And, tissues of soybean DT26 cultivar accumulated more proline under saline condition. Keywords: Soybean, Glycine max , DT26, salinity.